A Feasibility Study and Development Framework Design for Realizing Smartphone-based Vehicular Networking Systems - Park, Yongtae; Ha, Jihun; Kuk, Seungho; Kim, Hyogon; Liang, Chieh-Jan Mike; Ko, JeongGil (TMC (IEEE Transactions on Mobile Computing), 2014)
Designing and distributing effective vehicular safety applications can help significantly reduce the number of car accidents and assure the safety of many precious lives. However, despite the efforts from standardization bodies and industrial manufacturers, many studies suggest that it will take more than a decade for them to be fully deployed. We start this work with the hypothesis that smartphones may be suitable platforms for catalyzing the distribution of vehicular safety applications. Specifically, smartphones connected to their respective cellular networks can report their sensing data to back-end application servers and exchange safety related messages with surrounding vehicles. This paper first evaluates the performance of the vehicular ad-hoc networking standards and the hardware platforms that implement them. Next, we perform empirical evaluations on the performance of cellular networks to confirm their applicability in vehicular networking. Based on our observations, we present the VoCell application development framework. VoCell, comprehends a set of components that eases the development of smartphone applications for vehicular networking applications. Using VoCell, developers can easily access internal and external sensing components and share this data to servers on the cloud. We present a number of example applications developed using VoCell and evaluate their effectiveness in local and highway environments using a pilot deployment. We envision that VoCell can act as a building block for enabling new smartphone-based systems in the vehicular networking application domain.